Measuring the recovery of the Northern Benguela Current Large Marine Ecosystem (BCLME): An application of the DPSIR framework. (January 2016) - Mukuvari, Itai; Mafwila, Samuel Kakambi; Chimuka, Luke
Abstract: The objective of this paper is to describe the use of the Drivers, Pressures, State, Impact and Response (DPSIR) framework as a method for incorporating a multisector and multispecies approach for assessing progress in the recovery of a degraded Large Marine Ecosystem (LME). The Benguela Current Large Marine Ecosystem (BCLME) was degraded due to overfishing between 1960 and 1990. Various programmes were implemented to help the ecosystem to recover. These programmes included scientific studies, mechanisms to control exploitation of living marine resources, governance arrangements and capacity building. Progress made from these efforts was assessed using 3-year-moving average analyses and regression analyses of indicator trends. Twenty-seven indicators were analysed. The indicators chosen were based on the DPSIR framework and the modules of the LME approach. From the results, 41% of the indicators showed improvement of the ecosystem compared to 26% that showed continued degradation whilst the other 33% were neutral. Key improvement trends were seen in the slope values of indicators such as by-catch reduction 2566.42, total allowable catch (TAC) 7.63 and size abundances 0.60. Negative trends included biomass −170.24, and contribution of fisheries to GDP -0.35. Therefore, there were some negative effects but the BCLME is starting to show some signs of recovery. The results support the use of the LME approach as a sound way of addressing degraded marine ecosystems. The study also showed that using the DPSIR framework a multispecies, multidisciplinary approach can be achieved leading to a holistic review of the ecosystem. Highlights: DPSIR used to assess recovery of large marine ecosystem. The Benguela Current Large Marine Ecosystem (BCLME) was degraded due to overfishing. Results are important for management of Benguela Current Large Marine Ecosystem and other large marine ecosystem.